Nutritional composition of seasoning broths formulated from the edible mushroom Psathyrella tuberculata, onion (Allium cepa), garlic (Allium sativum), parsley (Petroselinum crispum) and cassava starch (Manihot esculenta) - Ouattara Ahmed FARMAN; N’zebo Désiré KOUAMÉ; Mah Laure Marie Régina KADJO; Anin Louise ANIN-ATCHIBRI; Thomas DADIÉ (Applied Food Research, 2025)
Industrial seasoning broths, containing around 50 % salt (NaCl) and monosodium glutamate, tend to mask saltiness and promote excessive sodium intake. Their frequent use is linked to high blood pressure, type 2 diabetes, and metabolic disorders. This study aimed to develop a healthier alternative using local natural ingredients with antihypertensive properties. Three seasoning broths were formulated using Psathyrella tuberculata (an edible wild mushroom used as a flavour enhancer), onion, garlic, parsley, and cassava starch, based on a matrix algorithm in Excel. Their nutritional composition was assessed in vitro using standard methods. The in vitro levels of bioactive nutrients involved in blood pressure regulation varied depending on the formulations: protein (16.07±0.01 to 23.94±0.02 %), fiber (22.04±0.40 to 26.07±0.15 %), potassium (4737.11±0.43 to 8858.39±0.58 mg/100 g DM), sodium (100.02±0.01 to 145.04±0.15 mg/100 g DM), calcium (1094.64±0.80 to 1595.11±0.49 mg/100 g DM), magnesium (1112.57±0.41 to 1524.04±0.99 mg/100 g DM), flavonoids (6.45±0.44 to 7.46±0.65 mg EQ/100 g DM) and polyphenols (105.61±0.50 to 220.30±0.58 mg EAG /100 g DM). Ratios of phytate/calcium, phytate/magnesium, and oxalate/calcium were all below 1, indicating low levels of antinutritional factors. These formulations could therefore be used as nutritional alternatives in the prevention and fight against arterial hypertension.